Cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel
By using crosslinked sodium hyaluronate microspheres and non-crosslinked sodium hyaluronate composite gel, the problem of the rapid non-degradation and absorption of existing soft tissue filling materials in the body is solved, and long-term filling effect and anti-aging effects are achieved, while reducing the occurrence of adverse reactions.
Patent Information
- Application Number
- CN202411809186.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
Existing soft tissue filling materials are not degradable in the body, causing long-term irritation of the body, poor biocompatibility, and prone to adverse reactions such as granuloma and allergies. At the same time, the absorption and degradation rate of bioabsorbable materials is too fast to stay in the body for a long time and cannot provide long-lasting structural support.
Crosslinked sodium hyaluronate microspheres were prepared by polymerization of crosslinked sodium hyaluronate by crosslinked sodium hyaluronate, combining non-crosslinked sodium hyaluronate and recombinant type III collagen to form a composite gel. Cross-linked sodium hyaluronate microspheres degrade within 1-3 years, providing long-term filling effects and stimulating the production of collagen in the body.
It achieves long-term filling effect in the body, reduces the occurrence of adverse reactions, such as granuloma and allergies, and achieves the effect of anti-aging and preventing aging by stimulating collagen production.
Smart Images

Figure CN119607262A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of medical interventional treatment materials, and more specifically, to a cross-linked sodium hyaluronate microsphere and a non-cross-linked sodium hyaluronate composite gel. Background Art
[0002] Soft tissue filling plays a major role in improving the appearance of aging skin or treating local soft tissue defects caused by deformity, trauma, or surgery. Especially for patients with aging faces who want to have a younger face, soft tissue filling has become increasingly popular in recent years because it is simple to operate, low cost, and has a short recovery time. It does not require surgery and does not affect daily work and life.
[0003] Injectable fillers can be broadly divided into four categories: 1. The first category is non-absorbable materials: paraffin, silicone oil, and polymethyl methacrylate (PMMA). Although these materials can provide long-lasting and reliable soft tissue filling effects, they cannot be degraded and absorbed in the body, will cause long-term stimulation to the body, have poor biocompatibility, and are prone to induce granulomas and other serious adverse reactions in the body.
[0004] 2. The second category is bioabsorbable materials with a single ingredient, such as hyaluronic acid, which are widely present in the human body and can be completely metabolized and degraded by the human body, but their absorption and degradation rate is often very fast and they cannot stay in the body for a long time.
[0005] 3. The third category is synthetic absorbable microsphere products, such as polycaprolactone (PCL), poly L-lactic acid (PLLA) and hydroxyapatite (CaHA) microspheres. Compared with traditional soft tissue filling materials such as HA, this type of material has better mechanical properties and is not easily degraded by the body. It can provide better and more lasting structural support for soft tissue. However, improper operation or too shallow injection level may cause adverse reactions such as delayed nodules and granulomas. Summary of the invention
[0006] In order to prolong the degradation time while reducing the occurrence of adverse reactions, the present application provides a cross-linked sodium hyaluronate microsphere and a non-cross-linked sodium hyaluronate composite gel.
[0007] In the first aspect, the present application provides a cross-linked sodium hyaluronate microsphere and a non-cross-linked sodium hyaluronate composite gel, using the following technical solution: A cross-linked sodium hyaluronate microsphere and a non-cross-linked sodium hyaluronate composite gel, comprising the following components in percentage by weight: Cross-linked sodium hyaluronate microspheres 10-50%; Non-cross-linked sodium hyaluronate 2-10%; Recombinant type III collagen 2-10%; Licardoine 0.05-0.2%; Water balance; The cross-linked sodium hyaluronate microspheres are obtained by polymerization of methacryloyl sodium hyaluronate as a raw material.
[0008] By adopting the above technical solution: the composite gel of the present application contains: non-cross-linked sodium hyaluronate and recombinant type III collagen can fill wrinkles in the short term, while cross-linked sodium hyaluronate microspheres can achieve long-term filling effects within 1-3 years, and can stimulate the body's own collagen production to achieve anti-aging and anti-aging effects. Due to the excellent biocompatibility of sodium hyaluronate, various adverse reactions such as granulomas, allergies, etc. can be avoided.
[0009] At the same time, the microspheres modified with sodium methacrylate hyaluronate have the advantage of good compression elasticity.
[0010] Optionally, the specific preparation method of the cross-linked sodium hyaluronate microspheres is: Adding methacryloyl sodium hyaluronate and an initiator to water, and mixing to obtain an aqueous phase; adding a dispersant to an oily liquid and mixing to obtain an oil phase; After nitrogen is purged through the oil phase, the aqueous phase is added dropwise under the condition of mechanical stirring while maintaining the nitrogen atmosphere, and the temperature is raised to 40-60°C for reaction for 6-8h, and the product is filtered, washed, and sieved to obtain the product.
[0011] By adopting the above technical solution: methacryloyl sodium hyaluronate is polymerized under initiator conditions to form cross-linked sodium hyaluronate microspheres, and the cross-linked microspheres degrade slowly and can be degraded within 1-3 years.
[0012] Optionally, the initiator is ammonium persulfate, and the weight ratio of ammonium persulfate to sodium methacrylate hyaluronate is 0.5-1.5:100.
[0013] By adopting the above technical solution: ammonium persulfate initiates the polymerization reaction of methacryloyl sodium hyaluronate. When the ammonium persulfate content is less than 0.5%, the polymerization rate is low and the reaction is incomplete. When the content is higher than 1.5%, the initial polymerization rate is fast, the polymerization is uneven, and the microspheres are yellow in color.
[0014] Optionally, the oily liquid is butyl acetate or liquid paraffin; the dispersant is one of Span60, Span80, cellulose acetate, and EM-90, and the weight ratio of the dispersant to the oily liquid is 0.5-1.5:100.
[0015] By adopting the above technical solution: the amount of dispersant used can control the size of the microsphere particle size. When the dispersant content is lower than 0.5%, the microsphere particle size is greater than 60um, and when the dispersant content is higher than 1.5%, the microsphere particle size is less than 30um.
[0016] Optionally, the volume ratio of the water phase to the oil phase is 1:(3-10).
[0017] By adopting the above technical solution: the water-oil ratio can control the size of the microsphere particle size. When the water-oil ratio is greater than 1:3, the microsphere particle size is relatively large. When the water-oil ratio is less than 1:10, the microsphere particle size is relatively large. When the water-oil ratio is controlled at 1:(3-10), the proportion of microsphere particles with a diameter of 30-60um is higher.
[0018] Optionally, the mechanical stirring speed is 300-600 rpm.
[0019] By adopting the above technical solution: the stirring speed can control the size of the microsphere particles. When the stirring speed is lower than 300rpm, the microsphere particles with a diameter greater than 60um tend to be more, and when the stirring speed is higher than 600um, the microsphere particles with a diameter less than 30um tend to be more.
[0020] Optionally, the particle size of the cross-linked sodium hyaluronate microspheres is 30-60 um.
[0021] By adopting the above technical solution: when the particle size of the microsphere is less than 30um, it is easy to be phagocytosed by macrophages, and when the particle size of the microsphere is greater than 60um, the filling is not full and the injection is difficult.
[0022] Optionally, the raw materials for preparing the methacrylated sodium hyaluronate include methacrylic anhydride and sodium hyaluronate; the molecular weight of the sodium hyaluronate is 2000-100000Da.
[0023] By adopting the above technical solution: methacrylic anhydride reacts with the hydroxyl group in sodium hyaluronate to undergo esterification reaction, so that double bonds are grafted onto the main chain of sodium hyaluronate. When medium-low molecular weight sodium hyaluronate (2000-100000Da) is used, the reaction is more uniform.
[0024] Optionally, the molecular weight of the non-cross-linked sodium hyaluronate is 500,000-2,000,000 Da.
[0025] By adopting the above technical solution: when non-cross-linked sodium hyaluronate is injected into the body, it plays a short-term supporting role. When medium and high molecular weight (500,000-2,000,000 Da) is used, the supporting effect is 1-3 months.
[0026] In a second aspect, the present application provides a method for preparing cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel, using the following technical solution: A method for preparing a composite gel of cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate, comprising the following steps: S1. Preparation of methacryloyl sodium hyaluronate: add methacrylic anhydride, N,N-dimethylformamide and sodium hydroxide to a sodium hyaluronate aqueous solution, react at 25-40° C., then add sodium chloride, and after the reaction is complete, add anhydrous ethanol to precipitate, filter to remove the filtrate, wash and dry to obtain; S2. Preparation of cross-linked sodium hyaluronate microspheres: add methacrylated sodium hyaluronate and an initiator to water, mix to obtain a water phase; add a dispersant to an oily liquid, mix to obtain an oil phase; after nitrogen purging the oil phase, add the water phase dropwise under a nitrogen atmosphere and mechanical stirring, heat to 40-60° C., react for 6-8 hours, filter, wash, and sieve to obtain the microspheres; S3. Preparation of gel: add licardoine, non-cross-linked sodium hyaluronate and collagen into water, mix, then add cross-linked sodium hyaluronate microspheres, mix, vacuum exhaust, can, and sterilize to obtain a composite gel.
[0027] By adopting the above technical solution: fewer steps, simple and efficient process, it is conducive to industrial scale-up preparation of gel. At the same time, Licardoine can reduce the pain during injection, non-cross-linked sodium hyaluronate and collagen provide short-term support, degrade in 1-3 months, cross-linked sodium hyaluronate provides long-term support, 1-3 years, and long-term stimulation of cells to promote the production of their own collagen.
[0028] In summary, this application has the following beneficial effects: 1. The gel of the present application, which contains non-cross-linked sodium hyaluronate and recombinant type III collagen, can fill wrinkles and depressions in the short term, while the cross-linked sodium hyaluronate microspheres can achieve long-term filling effects within 1-3 years, and can stimulate the body's own collagen production to achieve anti-aging and anti-aging effects. Due to the excellent biocompatibility of sodium hyaluronate, various adverse reactions, such as granulomas, allergies, etc., can be avoided; 2. The cross-linked sodium hyaluronate microspheres in this application are made of sodium methacrylate hyaluronate as raw material, and the microspheres modified with sodium methacrylate hyaluronate have the advantage of good compression elasticity; 3. The method of the present application has fewer steps, simple and efficient process, and is conducive to industrial scale-up of gel preparation. At the same time, Licardoine can reduce the pain during injection, non-cross-linked sodium hyaluronate and collagen provide short-term support, degrade in 1-3 months, and cross-linked sodium hyaluronate provides long-term support, 1-3 years, and long-term stimulation of cells to promote the production of their own collagen. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1This is a photo of the cross-linked sodium hyaluronate microspheres prepared in Example 1. DETAILED DESCRIPTION
[0030] The present application is further described in detail below in conjunction with the examples. The sources of the components are as follows, except for the components specifically described below, the components are commercially available.
[0031] The sodium hyaluronate and non-cross-linked sodium hyaluronate in this application are both non-cross-linked sodium hyaluronate (essentially one substance, the different names are only for distinction, and the molecular weights are different). Sodium hyaluronate of various molecular weights (non-cross-linked sodium hyaluronate) are all collected from Shaanxi Chenming Biotechnology Co., Ltd.; Licardoine was obtained from Hubei Shishun Biotechnology Co., Ltd.; Recombinant type III collagen was obtained from Bloomage Biotech Co., Ltd., product name: Bloomcolla TM ColⅢ recombinant type III collagen; Polymethyl methacrylate microspheres were obtained from Hubei Maidehao Biotechnology Co., Ltd., model MDH; Polycaprolactone microspheres were obtained from Runmei Shiguang (Beijing) Biotechnology Co., Ltd., with a particle size of 20-50 μm; L-polylactic acid microspheres were obtained from Runmei Shiguang (Beijing) Biotechnology Co., Ltd. with a particle size of 20-50μm.
[0032] Example 1 A cross-linked sodium hyaluronate microsphere and a non-cross-linked sodium hyaluronate composite gel is prepared by the following steps: S1. Preparation of methacryloyl sodium hyaluronate: Sodium hyaluronate (molecular weight 2000Da) was dissolved in deionized water to obtain a sodium hyaluronate aqueous solution (concentration 0.02g / mL). 0.5L N,N-dimethylformamide and 10g methacrylic anhydride were added to 1L sodium hyaluronate aqueous solution, and sodium hydroxide was added to adjust the pH of the system to 9, and the mixture was stirred at 25°C for 24h, and then 4g sodium chloride was added for 0.5h, and 1L anhydrous ethanol was added for precipitation, and the filtrate was removed by filtration, and then anhydrous ethanol, 80% ethanol water, and 60% ethanol water were added in a 1:10 material-liquid ratio for gradient washing, and the gradient washing was repeated five times. The washed product was placed in a vacuum dryer at 40°C to obtain methacrylated sodium hyaluronate; S2. Preparation of cross-linked sodium hyaluronate microspheres: 2 g of methacryloyl sodium hyaluronate and 0.01 g of initiator (ammonium persulfate) were added to 100 mL of water and mixed to obtain an aqueous phase.
[0033] 0.5 g of dispersant (Span 60) was added to 100 g of oil-soluble liquid (butyl acetate), and the mixture was mixed to obtain an oil phase.
[0034] After purging 300mL of the oil phase with nitrogen, maintain the nitrogen atmosphere, and under the condition of mechanical stirring at a speed of 300rpm, add 100mL of water phase for reverse suspension to form an oil-in-water reverse suspension polymerization system. After the addition is completed, the polymerization system is heated to 40℃ and reacted for 6h. The filtrate is removed by suction, and clean water is added for washing once according to a solid-liquid ratio of 1:10. After sieving, cross-linked sodium hyaluronate microspheres with a particle size of 30-60um are obtained.
[0035] S3, preparation of gel: add licardoine, non-cross-linked sodium hyaluronate (molecular weight 500000Da), and recombinant type III collagen to water, stir and mix at 300rpm for 20min, then add cross-linked sodium hyaluronate microspheres, stir and mix at 200rpm for 10min, evacuate under vacuum, can, and sterilize to obtain a composite gel. The amount of each component in step S3 is shown in Table 1.
[0036] Example 2 A cross-linked sodium hyaluronate microsphere and a non-cross-linked sodium hyaluronate composite gel is prepared by the following steps: S1. Preparation of sodium methacrylated hyaluronate: Sodium hyaluronate (molecular weight 60000Da) was dissolved in deionized water to obtain a sodium hyaluronate aqueous solution (concentration 0.2g / mL). 1L N,N-dimethylformamide and 200g methacrylic anhydride were added to 1L sodium hyaluronate aqueous solution, and sodium hydroxide was added to adjust the pH of the system to 10. The mixture was stirred at 25°C for 24h, and then 40g sodium chloride was added to react for 0.5h. 1L anhydrous ethanol was added for precipitation, and the filtrate was removed by filtration. Anhydrous ethanol, 80% ethanol water, and 60% ethanol water were added in a 1:10 solid-liquid ratio for gradient washing. The gradient washing was repeated five times, and the washed product was dried under vacuum at 40°C to obtain sodium methacrylated hyaluronate. S2. Preparation of cross-linked sodium hyaluronate microspheres: 2 g of methacryloyl sodium hyaluronate and 0.02 g of initiator (ammonium persulfate) were added to 100 mL of water and mixed to obtain an aqueous phase.
[0037] Add 1 g of dispersant (Span 60) to 100 g of oily liquid (butyl acetate), and mix well to obtain an oil phase.
[0038] After purging 600mL of the oil phase with nitrogen, maintain the nitrogen atmosphere, and under the condition of mechanical stirring at a speed of 450rpm, add 100mL of water phase for reverse suspension to form an oil-in-water reverse suspension polymerization system. After the addition is completed, the polymerization system is heated to 40℃ and reacted for 6h. The filtrate is removed by suction, and clean water is added for washing once according to a solid-liquid ratio of 1:10. After sieving, cross-linked sodium hyaluronate microspheres with a particle size of 30-50um are obtained.
[0039] S3, preparation of gel: add licardoine, non-cross-linked sodium hyaluronate (molecular weight 1000000Da), and recombinant type III collagen to water, stir and mix at 300 rpm for 20 min, then add cross-linked sodium hyaluronate microspheres, stir and mix at 200 rpm for 10 min, vacuum exhaust, can, and sterilize to obtain a composite gel. The amount of each component in step S3 is shown in Table 1.
[0040] Example 3 A cross-linked sodium hyaluronate microsphere and a non-cross-linked sodium hyaluronate composite gel is prepared by the following steps: S1. Preparation of methacryloyl sodium hyaluronate: Sodium hyaluronate (molecular weight 100000Da) was dissolved in deionized water to obtain a sodium hyaluronate aqueous solution (concentration 0.4g / mL). 2L N,N-dimethylformamide and 800g methacrylic anhydride were added to 1L sodium hyaluronate aqueous solution, and sodium hydroxide was added to adjust the pH of the system to 11, and stirred at 40°C for 20h, and then 40g sodium chloride was added for 0.5h, and 1L anhydrous ethanol was added for precipitation, and the filtrate was removed by filtration, and then anhydrous ethanol, 80% ethanol water, and 60% ethanol water were added in a 1:10 material-liquid ratio for gradient washing, and the gradient washing was repeated five times, and the washed product was placed at 40°C and vacuum dried to obtain methacryloyl sodium hyaluronate; S2. Preparation of cross-linked sodium hyaluronate microspheres: 2 g of methacryloyl sodium hyaluronate and 0.03 g of initiator (ammonium persulfate) were added to 100 mL of water and mixed to obtain an aqueous phase.
[0041] 1.5 g of dispersant (Span 60) was added to 100 g of oily liquid (butyl acetate), and the mixture was mixed to obtain an oil phase.
[0042] After purging 1000mL of the oil phase with nitrogen, maintain the nitrogen atmosphere, and under the condition of mechanical stirring at a speed of 450rpm, add 100mL of water phase for reverse suspension to form an oil-in-water reverse suspension polymerization system. After the addition is completed, the polymerization system is heated to 40℃ and reacted for 6h. The filtrate is removed by suction, and clean water is added for washing once according to a solid-liquid ratio of 1:10. After sieving, cross-linked sodium hyaluronate microspheres with a particle size of 30-50um are obtained.
[0043] S3, preparation of gel: add licardoine, non-cross-linked sodium hyaluronate (molecular weight 2000000Da), and recombinant type III collagen to water, stir and mix at 300rpm for 20min, then add cross-linked sodium hyaluronate microspheres, stir and mix at 200rpm for 10min, vacuum exhaust, can, and sterilize to obtain a composite gel. The amount of each component in step S3 is shown in Table 1.
[0044] Comparative Example 1-2 A composite gel, which is different from Example 2 in that the amounts of the components are different, see Table 1 for details.
[0045] Table 1 Components and their weights in Examples 1-3 and Comparative Examples 1-2 (kg) Components Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Cross-linked Sodium Hyaluronate Microspheres 10 30 50 5 35 Non-cross-linked sodium hyaluronate 2 6 10 6 6 Recombinant collagen type Ⅲ 10 6 2 6 6 Licardoine 0.05 0.1 0.2 0.1 0.1 water 77.96 57.9 37.8 82.9 52.9 Comparative Example 3 A composite gel, which differs from Example 2 in that an equal amount of polymethyl methacrylate microspheres are used instead of cross-linked sodium hyaluronate microspheres.
[0046] Comparative Example 4 A composite gel, which differs from Example 2 in that an equal amount of polycaprolactone microspheres are used instead of cross-linked sodium hyaluronate microspheres.
[0047] Comparative Example 5 A composite gel, which differs from Example 2 in that an equal amount of L-polylactic acid microspheres are used instead of cross-linked sodium hyaluronate microspheres.
[0048] Comparative Example 6 A composite gel, which differs from Example 2 in that steps S1 and S2 are not performed, and in step S3, an equal amount of N-(2,2-dimethoxy)-2-methylacrylamide modified microspheres are used instead of cross-linked hyaluronic acid microspheres.
[0049] The method for preparing N-(2,2-dimethoxy)-2-methylacrylamide modified microspheres is as follows: 18.00 g of sodium hyaluronate (molecular weight 60000 Da) was added to 150 g of water, heated to 90° C. and stirred to dissolve, then 0.25 g of N-(2,2-dimethoxy)-2-methylacrylamide was added, and after stirring evenly, 12.5 g of sulfuric acid was added and stirred for 12 h, and then sodium hydroxide was added to neutralize to obtain a high molecular monomer aqueous solution; 7.00 g of sodium acrylate, 1.00 g of potassium persulfate and the polymer monomer aqueous solution were mixed, and a hydrochloric acid aqueous solution was added to adjust the pH value of the solution to obtain an aqueous phase with a pH of 2.5; Dissolve 20.00 g of cellulose acetate butyrate in 1200 g of ethyl acetate, and stir to dissolve at 35°C to obtain an oil phase; Under stirring conditions, the water phase was added dropwise to the oil phase to form an oil-in-water reverse suspension polymerization system. After the addition was completed, the reverse suspension polymerization system was heated to 85°C, and then 8.00 g of tetramethyldiamine was added. After reacting for 15 hours, the heating and stirring were stopped, the system was allowed to stand, the oil phase was separated after stratification, and the embolic microspheres were collected and washed repeatedly.
[0050] Performance Testing The following performance tests were performed on the composite gels prepared in the examples and comparative examples, and the test results are recorded in Table 2.
[0051] Detection Methods 1. Biocompatibility test: According to GB / T 16886.6-2022 "Biological evaluation of medical devices Part 6: Local reaction test after implantation".
[0052] 2. Anti-degradation ability experiment: Take 0.5 g of the non-cross-linked sodium hyaluronate and cross-linked sodium hyaluronate microsphere composite gels prepared in the example and the comparative example, add 2 ml of 300 U / ml hyaluronidase solution (the activity of hyaluronidase is 838 U / mg, sigma), keep warm at 37°C for degradation and start timing, detect the mass loss of the gel, and record the time when the mass loss reaches 50%, which is the effective filling time.
[0053] Table 2 Performance test results Referring to Table 2, the gels of Examples 1-3 contain non-cross-linked sodium hyaluronate and recombinant type III collagen, which can fill wrinkles and depressions in the short term, while cross-linked sodium hyaluronate microspheres can achieve long-term filling effects within 1-3 years, and can stimulate the body's own collagen production to achieve anti-aging and anti-aging effects, and there is no significant difference between the negative control group and the implanted 26 weeks. In Comparative Examples 3-6, equal amounts of polymethyl methacrylate microspheres, polycaprolactone microspheres, L-polylactic acid microspheres, and N-(2,2-dimethoxy)-2-methylacrylamide modified microspheres are used to replace cross-linked hyaluronic acid microspheres, respectively, and there are problems of moderate irritation and short effective filling time.
[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A composite gel of cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate, characterized in that: It is composed of the following components in weight percentage: Cross-linked sodium hyaluronate microspheres 10-50%; Non-cross-linked sodium hyaluronate 2-10%; Recombinant type III collagen 2-10%; Licardoine 0.05-0.2%; Water balance; The cross-linked sodium hyaluronate microspheres are obtained by polymerization of methacryloyl sodium hyaluronate as a raw material.
2. The cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel according to claim 1, characterized in that: The specific preparation method of the cross-linked sodium hyaluronate microspheres is: Adding methacryloyl sodium hyaluronate and an initiator to water, and mixing to obtain an aqueous phase; adding a dispersant to an oily liquid and mixing to obtain an oil phase; After nitrogen is purged through the oil phase, the aqueous phase is added dropwise under the condition of mechanical stirring while maintaining the nitrogen atmosphere, and the temperature is raised to 40-60°C for reaction for 6-8h, and the product is filtered, washed, and sieved to obtain the product.
3. The cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel according to claim 2, characterized in that: The initiator is ammonium persulfate, and the weight ratio of ammonium persulfate to methacrylated sodium hyaluronate is 0.5-1.5:
100.
4. The cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel according to claim 2, characterized in that: The oily liquid is butyl acetate or liquid paraffin; the dispersant is one of Span60, Span80, cellulose acetate, and EM-90, and the weight ratio of the dispersant to the oily liquid is 0.5-1.5:
100.
5. The cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel according to claim 2, characterized in that: The volume ratio of the water phase to the oil phase is 1:(3-10).
6. The cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel according to claim 2, characterized in that: The mechanical stirring speed is 300-600 rpm.
7. The cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel according to claim 2, characterized in that: The particle size of the cross-linked sodium hyaluronate microspheres is 30-60 um.
8. The cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel according to claim 1, characterized in that: The raw materials for preparing the methacrylated sodium hyaluronate include methacrylic anhydride and sodium hyaluronate; the molecular weight of the sodium hyaluronate is 2000-100000Da.
9. The cross-linked sodium hyaluronate microspheres and non-cross-linked sodium hyaluronate composite gel according to claim 1, characterized in that: The molecular weight of the non-cross-linked sodium hyaluronate is 500,000-2,000,000 Da.
10. A method for preparing the cross-linked sodium hyaluronate microspheres and the non-cross-linked sodium hyaluronate composite gel according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preparation of methacryloyl sodium hyaluronate: add methacrylic anhydride, N,N-dimethylformamide and sodium hydroxide to a sodium hyaluronate aqueous solution, react at 25-40° C., then add sodium chloride, and after the reaction is complete, add anhydrous ethanol to precipitate, filter to remove the filtrate, wash and dry to obtain; S2. Preparation of cross-linked sodium hyaluronate microspheres: add methacrylated sodium hyaluronate and an initiator to water, mix to obtain a water phase; add a dispersant to an oily liquid, mix to obtain an oil phase; after nitrogen purging the oil phase, add the water phase dropwise under a nitrogen atmosphere and mechanical stirring, heat to 40-60° C., react for 6-8 hours, filter, wash, and sieve to obtain the microspheres; S3. Preparation of gel: add licardoine, non-cross-linked sodium hyaluronate and collagen into water, mix, then add cross-linked sodium hyaluronate microspheres, mix, vacuum exhaust, can, and sterilize to obtain a composite gel.